Multiple factors behind early diversification of skull morphology in the continental radiation of New World monkeys. (1st December 2018) - Aristide, Leandro; Bastide, Paul; dos Reis, Sergio Furtado; Pires dos Santos, Thaís M.; Lopes, Ricardo T.; Perez, S. Ivan
Abstract: Understanding the origin of diversity is a fundamental problem in evolutionary biology. The null expectation for the evolutionary diversification is that all changes in biological diversity are the result of random processes. Adaptive radiations depart from this expectation as ecological factors and natural selection are supposed to play a central role in driving exceptional diversification. However, it is not well understood how large‐scale continental radiations, given their characteristics, fit to these opposing theoretical models. Here, we used phylogenetic comparative methods and geometric morphometrics to study the evolutionary process of cranial diversification in the continental radiation of New World monkeys. Particularly, we tested several alternative evolutionary scenarios for morphological evolution in the clade. Results indicated that despite the platyrrhine radiation being old and geographically widespread, the formative patterns arising from the initial stages of diversification probably associated with an adaptive radiation can still be recognized today. We also show that no single explored factor (e.g., ecological or allometric) can be invoked as a complete explanation for the observed phenotypic diversity patterns in the clade and, moreover, that different cranial regions exhibit particular macroevolutionary patterns. Together, our results highlight the evident complexity behind large‐scale evolutionary radiations.